Federalismo fundiário no crescimento econômico de Roraima - Viana, Alex Moura (2016)
The purpose of this dissertation is to study the possible relations between the economic growth of Roraima and the Brazilian federal institutional arrangement. To achieve this goal, the study analyzes the concept of federalism and the concept of property as well as its historical evolution as a set of rules and the distribution of state power over a given territory. The productive use of land and protected areas (indigenous lands, conservation units, military areas). In addition, there is also the presentation and historical evolution of the relationship between the union and the state of Roraima, in the field of land regularization in the light of federal land tenure. It explains the transformation of Roraima into a federative State and the land tenure in force. It seeks to evidence the land regularization in the state of Roraima, by Laws 10,304 / 2001 (Lei Marluce), with the edition of Law 11349/2009 and property rights. There is a need to seek information. By means of a bibliographic research of a qualitative nature, where it is sought to highlight the issues of social problems on the perspective of the land issue in the State of Roraima. In this way one immerses in the works of consecrated authors to understand the theory and relate it to the practice.